2012
DOI: 10.1128/jvi.00787-12
|View full text |Cite
|
Sign up to set email alerts
|

Cohesins Repress Kaposi's Sarcoma-Associated Herpesvirus Immediate Early Gene Transcription during Latency

Abstract: Chromatin-organizing factors such as CTCF and cohesins have been implicated in the control of complex viral regulatory programs. We investigated the role of CTCF and cohesins in the control of the switch from latency to the lytic cycle for Kaposi's sarcoma-associated herpesvirus (KSHV). We found that cohesin subunits but not CTCF are required for the repression of KSHV immediate early gene transcription. Depletion of the cohesin subunits Rad21, SMC1, and SMC3 resulted in lytic cycle gene transcription and vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
114
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(124 citation statements)
references
References 86 publications
9
114
1
Order By: Relevance
“…These data suggest that modulation of the chromatin in the Rta promoter is a critical mechanism for regulating the KSHV latent/lytic switch. During latency, Rta's 3.0-kb promoter is decorated with histones that bear modifications associated with both repression of transcription (histone H3 trimethylated at lysine 27 [H3K27-me3] and H3K9-me3) and activation of transcription (acetylation of histone H3 [H3K9/K14-ac] and H3K4-me3) (19)(20)(21)(22). A similar pattern of bivalent histone modifications is seen on cellular genes that are transcriptionally repressed but are poised to respond to signals that switch on their transcription (23).…”
Section: K Aposi's Sarcoma (Ks)-associated Herpesvirus (Kshv) Is Thementioning
confidence: 99%
“…These data suggest that modulation of the chromatin in the Rta promoter is a critical mechanism for regulating the KSHV latent/lytic switch. During latency, Rta's 3.0-kb promoter is decorated with histones that bear modifications associated with both repression of transcription (histone H3 trimethylated at lysine 27 [H3K27-me3] and H3K9-me3) and activation of transcription (acetylation of histone H3 [H3K9/K14-ac] and H3K4-me3) (19)(20)(21)(22). A similar pattern of bivalent histone modifications is seen on cellular genes that are transcriptionally repressed but are poised to respond to signals that switch on their transcription (23).…”
Section: K Aposi's Sarcoma (Ks)-associated Herpesvirus (Kshv) Is Thementioning
confidence: 99%
“…Previous studies have shown that CTCF binding sites in the KSHV latency control region compromise viral episome maintenance (26) and alter latency transcription control, including deregulation of LANA and derepression of lytic transcripts for K14/vGPCR (34,35). Other studies revealed that CTCF and cohesin mediate interactions between the latent and lytic control regions (35) and that the loss of cohesin, but not CTCF, leads to derepression of lytic immediateearly gene transcription (34). Whether the DNA-looping function and chromatin-organizing activity of CTCF are related to histone modifications, RNAPII binding, or RNA processing has not been resolved.…”
mentioning
confidence: 99%
“…In addition, CTCF can interact with RNA polymerase II (RNAPII) (31), alter nucleosome positions and histone variant enrichment (32), and influence histone modification patterns (33). Previous studies have shown that CTCF binding sites in the KSHV latency control region compromise viral episome maintenance (26) and alter latency transcription control, including deregulation of LANA and derepression of lytic transcripts for K14/vGPCR (34,35). Other studies revealed that CTCF and cohesin mediate interactions between the latent and lytic control regions (35) and that the loss of cohesin, but not CTCF, leads to derepression of lytic immediateearly gene transcription (34).…”
mentioning
confidence: 99%
“…Whilst not yet demonstrated in alphaherpesviruses, stress-induced dissociation of CTCF/cohesin leading to release of paused RNA polymerase II in early stages of latent Kaposi's sarcoma-associated herpesvirus (human herpesvirus 8) reactivation has been documented (Kang & Lieberman, 2011;Chen et al, 2012). Overall, epigenetic regulation of latent HSV-1 gene transcription is an exquisite mechanism through which virus can undergo rapid animation in response to cellular stress, resulting in transcription of multiple genes independent of de novo protein synthesis.…”
Section: Alphaherpesvirus Gene Transcription Is Deregulated During VImentioning
confidence: 99%